Flowering phenology, fruit set and seed mass and number of five co-existing Gymnocalycium (Cactaceae) species from Córdoba mountain, Argentina - Giorgis, Melisa Adriana (2015)
Flowering phenology may play a critical role in plant coexistence, allowing not only a temporal partitioning of resources but also conditioning the relationship between seed mass and number among species. We analyzed how flowering phenology was related to seed mass and number, and how seed traits were related among them along these co-occurring species, in two consecutive flowering seasons. The flowering strategies of each species were characterized in terms of timing (onset and peak), duration, and flowering synchronicity among the five species. We found different flowering timing and flowering strategies among species. We found that the earliest flowering species showed higher reproductive success than species flowering later, but we did not find a clear relationship among flowering timing and seed size. However a clear trade of between seed mass and number among species was highlight, as species with higher seed mass produced a lower number of seeds per fruit and individual, while species with lower seed mass had higher seed number.